Cocaine and Heroin in Europe 1983-93. A cross-national comparison of trafficking and prices - Farrell, Graham (The British journal of criminology, 1996)
Drug law enforcement aims to reduce the consumption of illicit drugs through reducing supply and increasing prices. Data on cocaine and heroin seizures, prices, and methods of trafficking are presented for 1983-93. Seizures, giving some indirect indicator of trafficking, rose sharply for both drugs in the second half of the the 1980s. Prices of both drugs showed a decline across the decade, and the prices of both drugs seemed to track each other. Data on the primary means of transport of cocaine and heroin into Europe lends support to an explanation of the price patterns in terms of the risk factors these impose for traffickers. The nature of the trafficking, and the mechanism by which enforcement of trafficking laws is intended to impact upon the problem, suggest that the rapid substitution of interdictedtraffickers androutes is highly likely, and that present levels of enforcement will have little deterrent or preventive impact. While the European drug scene is changing rapidly, not least due to political changes, the analysis may retain some general applicability